Dangerous Animals and the Asian Martial Arts - Dohrenwend, Robert E. (Revista de Artes Marciales Asiáticas, 2012)
In spite of legends to the contrary, the unarmed fighting arms did not originate as protection against attacks by wild animals. The modern unarmed martial arts have no techniques devised to counter an attack by any animal, wild or domestic. An attack by an animal is extremely dangerous; it is at least as likely as an attack by another human being, and there is little that you can do if unarmed. This introduction to animal attacks, based on personal experience and published accounts, is written to emphasize this gap in our training, in the hope that the reader will take steps to become less vulnerable.